Influence of Discharge and ?h?nn?l G??m?try on S????g? Losses from S???nd?ry ??n?l - Shаikh, Nооr Mustаfа; Mаngriо, Munir Аhmеd; Tаlрur, Mаshооquе Аli; Issаni, Mushtаq Аhmеd (PSM Biological Research, 2018)
S????g? is th? m?st serious f?rms ?f w?t?r loss in ?n irrig?ti?n ??n?l n?tw?rk. S????g? l?ss m?stly d???nd ?n th? ?h?nn?l g??m?try. ?x??ssiv? s????g? l?ss?s ??n ??us? w?t?r l?gging ?nd s?il s?linity du? t? whi?h th? ?ultiv?bl? ?r? r?du??d, ?nd r?sults in ? l?ss ?f ??t?nti?l ?r?? ?r?du?ti?n. In this ????r, s????g? l?ss fr?m ? (S?rki Min?r) th?t ?ff t?k?s fr?m Sh?hu br?n?h ?f J?m?r?? ??n?l w?s d?t?rmin?d. R?l?v?nt hydr?uli? d?t? w?s r???rd?d ?t str?t?gi? l???ti?ns ?nd s????g? l?ss?s w?r? m??sur?d by infl?w- ?utfl?w m?th?d r?s???tiv?ly. Lin??r r?gr?ssi?n w?s ?m?l?y?d t? d?v?l??? ?m?iri??l r?l?ti?ns f?r ??m?uting s????g? l?ss?s with r?s???t t? ?h?nn?l g??m?try. ??-Ty?? ?nd ?ygmy ?urr?nt m?t?rs w?s us?d t? m??sur? th? dis?h?rg? ?t th? diff?r?nt s??ti?n. Th? r???rd?d d?t? ?f hydr?uli? ?h?r??t?risti?s w?s ??rr?l?t?d using lin??r r?gr?ssi?n ?n?lysis t? d?v?l?? ?n ?m?iri??l ?qu?ti?n f?r s????g? l?ss?s with ?h?nn?l g??m?try ??r?m?t?rs.Th? results r?v??l?d th?t th? m?ximum s????g? l?ss?s w?r? ?t 0-5RD (4%) f?ll?w?d by 5-10RD (3.4%), 10-15RD (3.4%) 15-20RD (3.5%), ?nd th?n 20-25RD (2.9%) ?nd ?v?r ?ll s????g? l?ss?s w?s 17% in th? min?r. Statistical analysis (LRA) shows significantly positive relationship at (?<0.05) f?r s????g? l?ss?s and dis?h?rg? (r2=0.962), w?tt?d ??rim?t?rs (r2=0.943), fl?w ?r?? (r2=0.914) ?nd t?? width (r2=0.967). Th?s? ?qu?ti?ns ??uld b? us?d t? ?stim?t? ??n?l s????g? l?ss?s with?ut g?ing thr?ugh th? ??nv?nti?n?l m?th?d.